CFD modelling of biogas mixing in an anaerobic digester used in wastewater treatment (2015)
Anaerobic digesters are widely used in the field of wastewater treatment for the reason that they allow for the stabilization of biological load in the treated flows. At the same time, these digesters produce biogas, which can be used as a renewable energy source. One of the most influencing variables, both in the digestion process as well as in biogas yield, is mixing and nowadays, one of the most implemented methods for mixing is the injection of the biogas produced by them (recirculation). Therefore, this project sought to study this mixing technique and its influence in the level of digestions achieved. The study found that the analysed real scale digester provides with adequate levels of mixing and that methane production may result in feasible economical applications.